2011
DOI: 10.1021/tx200011k
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Tungsten in Mice Following Oral Exposure to Sodium Tungstate

Abstract: Heavy metal tungsten alloys have replaced lead and depleted uranium in many munitions applications, due to public perception of these elements as environmentally unsafe. Tungsten materials left in the environment may become bioaccessible as tungstate, which might lead to population exposure through water and soil contamination. Although tungsten had been considered a relatively inert and toxicologically safe material, recent research findings have raised concerns about possible deleterious health effects after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…As there remains a lack of toxicological data, tungsten was nominated as an emerging contaminant for further investigation by the US Environmental Protection Agency and National Toxicity Program. 4 When mice ingest solubilized tungsten in the form of orthotungstate (WO 4 2− ), it rapidly accumulates in their bones 5 . Other bone-accumulating metals, such as lead and strontium 6 , substitute for calcium in hydroxyapatite, the calcium-phosphate matrix of bone, and can be removed using standard chelation therapy 7 .…”
mentioning
confidence: 99%
“…As there remains a lack of toxicological data, tungsten was nominated as an emerging contaminant for further investigation by the US Environmental Protection Agency and National Toxicity Program. 4 When mice ingest solubilized tungsten in the form of orthotungstate (WO 4 2− ), it rapidly accumulates in their bones 5 . Other bone-accumulating metals, such as lead and strontium 6 , substitute for calcium in hydroxyapatite, the calcium-phosphate matrix of bone, and can be removed using standard chelation therapy 7 .…”
mentioning
confidence: 99%
“…Studies have been performed to investigate the toxicity of tungsten or Na 2 WO 4 [43,44]. The concentration of Na 2 WO 4 used to evaluate the antidiabetic effect was around 6 mM [18,19].…”
Section: Figmentioning
confidence: 99%
“…The distribution of tungsten in the body of mice 24 h after oral uptake of sodium tungstate was studied by Guandalini et al 321 They used highresolution ICP-SFMS to quantify the metal in several organs such as liver, kidney, colon, spleen, brain and bone, which were digested using HNO 3 and H 2 O 2 prior to analysis. It could be shown that tungstate predominantly accumulates in bone and spleen.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 99%